Rejecting the Policy of Granting Tax Incentives to Donor Companies: Compelling Justifications - Younis A. Battal Saleh (Journal of Accounting Science, 2026)
General Background: Corporate social responsibility (CSR) is widely understood as a firm’s ethical commitment to society that extends beyond the pursuit of profit. Specific Background: In many countries, however, tax incentive policies for corporate donors may reshape this understanding by linking socially oriented activities to fiscal benefits. Knowledge Gap: Although the intersection between tax policy and CSR has become increasingly important, prior studies have not adequately clarified how such incentives may conceptually distort the meaning of CSR. Objective: This article therefore seeks to explain the forms of distortion generated by policies that provide tax incentives to corporate donors. Methods: To do so, the study applies logical justification and rational argumentation to evaluate whether these policies are consistent with the substantive principles of CSR. Results: The analysis indicates that tax incentive policies can distort CSR by encouraging firms to prioritize financial advantage over ethical commitment and by weakening the normative basis of social responsibility. This distortion is also shown to be inconsistent with the concepts of corporate social costs, stakeholder theory, corporate social contract theory, and tax justice. Novelty: Accordingly, this article offers a critical perspective on the relationship between tax policy and CSR, an issue that remains insufficiently explored in the literature. Implications: The findings contribute to CSR and tax scholarship and provide conceptual considerations that may inform reforms in the tax treatment of corporate donations to prevent further erosion of CSR principles.